Nanotherapy for Neural Retinal Regeneration - Chuyao Yu; Li Dong; Yujia Lv; Xuhan Shi; Ruiheng Zhang; Wenda Zhou; Haotian Wu; Heyan Li; Yitong Li; Zhou Li; Dan Luo; Wen‐Bin Wei (Advanced Science, 2025)
Abstract Retinal diseases can severely impair vision and even lead to blindness, posing significant threats to both physical and mental health. Physical retinal regenerative therapies are poised to revolutionize the treatment of various disorders associated with blindness. However, these therapies must overcome the challenges posed by the protective inner and outer blood‒retinal barriers. Nanotechnology applications in ophthalmology have shown great potential in addressing the issue of drug delivery to the eye. Moreover, nanotechnology‐based therapeutics can have profound clinical impacts on retinopathy, particularly retinal regeneration, thereby improving patient outcomes. Continuous advancements in nanotechnology are being applied to regenerate lost or damaged eye tissues and to treat vision loss and blindness caused by various retinal degenerative diseases. These approaches can be categorized into three main strategies: i) nanoparticles for delivering drugs, genes, and other essential substances; ii) nanoscaffolds for providing biocompatible support; and iii) nanocomposites for enhancing the functionality of primary or stem cells. The aim of this comprehensive review is to present the current understanding of nanotechnology‐based therapeutics for retinal regeneration, with a focus on the perspective functions of nanomaterials.